(untitled) (LACCEI, 2024)
The purpose of the research below is to determine how biotrade and sustainable business influence companies in Latin America. The sources of information used in the choice of records on a systematic review are: Redalyc, Base, Dialnet, Scielo, Google Scholar, Ebsco. The points of view that were taken into account in the contributions and discards in the literature are: diffusion time, if the investigations had an IMRD (introduction, methods, effects, debate) form. As a result, 30 investigations were selected, in which the most relevant contributions of each author were analyzed and subsequently extracted, then we classified them according to their importance. Finally, we conclude that trends in sustainable business and biotrade manage to maximize benefits in Latin American companies, either in the equitable distribution of profits to the company and the sectors that contribute to it, as well as increasing sustainability within of companies, collaborating with the environment and society